The Right to Freedom of Association for Public and Private Sector Employees in Zimbabwe in the Context of International Labour Organisation Standards - Maringe, Noah; Budeli-Nemakonde, Mpfari (Comparative and International Law Journal of Southern Africa, 2023)
This article deals with the right of employees to freedom of association in Zimbabwe. It adopts a comparative analysis with the International Labour Organisation’s (ILO) standards on freedom of association. In order to achieve this, lessons are drawn from South African labour law and practice since Zimbabwe’s constitutional provisions on freedom of association are similar to those of South Africa. It begins by discussing important sources of the right to freedom of association under the ILO framework which includes relevant Conventions. Zimbabwe adopted a new constitution in 2013 which incorporates the right of employees to freedom of association and all its components under the Declaration of Rights. This is a significant point of departure in analysing the extent to which Zimbabwe complies with its ILO obligations on freedom of association. The constitution applies to both public and private sector employees. However, pieces of legislation which give effect to the constitutional right to freedom of association create a two-tier labour relations system where public sector employees have different laws which govern them. On the other hand, private sector employees fall under the Labour Act. This necessitates a separate consideration of the key provisions which have a direct impact on the enjoyment of the right of employees to freedom of association in Zimbabwe in order to test their constitutionality.